Renaissance Pedagogy, Dedication of Life, and the School of Life: Soekarno's Thoughts on Education - Wawan Darmawan; Agus Mulyana; Wildan Insan Fauzi (Paramita: Historical Studies Journal, 2023)
Soekarno was an important figure in Indonesian history whose philosophy had contributed significantly to Indonesian development. Many studies have been carried out on Soekarno’s biography and historical narratives that had an impact on a global scale. However, the study of his thoughts and philosophy regarding education requires much more elaboration. The method used in this study is a historical method, done by exploring archival sources from ANRI (National Archives of the Republic of Indonesia) in the form of Soekarno's speeches at various activities. These archives sufficiently describe Soekarno's thoughts on education. The exploration of Soekarno's philosophy and thoughts in this article is focused on more general aspects of education. From exploring various sources, especially Soekarno's speeches, several themes extracted from his thoughts regarding the philosophy of education, national education, Islamic education, the relationship between pure and applied science, as well as the relationship between science, ideology, struggle, and social welfare were obtained.Soekarno adalah tokoh penting dalam sejarah Indonesia yang filsafatnya telah memberikan kontribusi signifikan terhadap pembangunan Indonesia. Banyak kajian yang dilakukan terhadap biografi dan narasi sejarah Sukarno yang berdampak pada skala global. Namun kajian pemikiran dan filosofinya mengenai pendidikan memerlukan penjabaran lebih lanjut. Metode yang digunakan dalam penelitian ini adalah metode sejarah, dilakukan dengan menggali sumber arsip dari ANRI (Arsip Nasional Republik Indonesia) berupa pidato-pidato Soekarno di berbagai kegiatan. Arsip-arsip ini cukup menggambarkan pemikiran Bung Karno mengenai pendidikan. Eksplorasi filosofi dan pemikiran Soekarno dalam artikel ini difokuskan pada aspek pendidikan yang lebih umum. Dari penelusuran berbagai sumber, khususnya pidato-pidato Soekarno, tersarikan beberapa tema pemikirannya mengenai filsafat pendidikan, pendidikan nasional, pendidikan Islam, hubungan ilmu murni dan ilmu terapan, serta hubungan ilmu pengetahuan, ideologi, perjuangan, dan kesejahteraan masyarakat. didapatkan.